Muslim Perception on Online Zakat Usage in Kuala Lumpur - Jamaludin, N.; Abd Wahab, N.; Hamed, A. B. (Universiti Sains Islam Malaysia, 2024)
This paper aims to examine the relationship of perceived usefulness, perceived ease of use, security and privacy and trust on online zakat usage. A survey approach has been adopted in this study where the data were collected via structured questionnaire. The questionnaire was distributed to 360 respondents of private and government employees in Kuala Lumpur, Malaysia. In this, the researchers developed a new construct in measuring the online zakat usage. The data were then quantitatively analyzed using SPSS program. The finding shows that all independent variables are correlated significantly with online zakat usage. Further analysis using multiple regression analysis indicates that only trust, perceived ease of use and perceived usefulness, are important in encouraging online zakat in terms of online zakat usage in the future.